2016
DOI: 10.1063/1.4968185
|View full text |Cite
|
Sign up to set email alerts
|

Si:SrTiO3-Al2O3-Si:SrTiO3 multi-dielectric architecture for metal-insulator-metal capacitor applications

Abstract: Metal-insulator-metal (MIM) capacitor structures, utilizing high-k materials having high dielectric constant and low dissipation factor, as charge storage and noise reduction media for adequate storage capacitance with reduced feature size (equivalent scaling) have attracted the interest of researchers due to their potential applications in dynamic random access memory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…At cryogenic temperatures and GHz frequencies, capacitance per area is c = 13.86 ± 0.14 fF/µm 2 . The difference between capacitance per area for different measurements could be explained by permittivity ε dependence on frequency, which have been observed [48][49][50], and temperature influence assumed to be small [29]. The reason why the extracted dielectric permittivity (ε RT = 30 ± 5 and ε LT = 19 ± 3) is higher than the conventional value ε ∼ 10 could be explained by high-ε inclusion (oxygen-depleted aluminum oxide or even incompletely oxidized aluminum) [48,51].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…At cryogenic temperatures and GHz frequencies, capacitance per area is c = 13.86 ± 0.14 fF/µm 2 . The difference between capacitance per area for different measurements could be explained by permittivity ε dependence on frequency, which have been observed [48][49][50], and temperature influence assumed to be small [29]. The reason why the extracted dielectric permittivity (ε RT = 30 ± 5 and ε LT = 19 ± 3) is higher than the conventional value ε ∼ 10 could be explained by high-ε inclusion (oxygen-depleted aluminum oxide or even incompletely oxidized aluminum) [48,51].…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, the dielectric permittivity ε is highly frequency dependent, that has been predicted [12] as ε(ω) = ε ∞ + εs−ε∞ 1+ω 2 τ 2 , where ε s and ε ∞ are static and high-frequency dielectric constants, τ is the characteristic energy relaxation time responsible for dissipation. Previous studies has been reported [12,[48][49][50][51] that the dielectric permittivity ε of AlO x changes by 25%-50% from 1 kHz to 1 MHz. We conclude that the difference between capacitance per area for different measurements can be explained by dielectric permittivity ε frequency dependence.…”
Section: Discussionmentioning
confidence: 95%